2011
DOI: 10.1071/py10032
|View full text |Cite
|
Sign up to set email alerts
|

'Adolescence is difficult, some kids are difficult': general practitioner perceptions of working with young people

Abstract: General practitioners (GPs) are the health care providers from which young people are most likely to seek help. However, the rate at which young people access GPs is less than ideal. Four focus groups were conducted with groups of GPs in New South Wales to inform the development of a GP training program on youth health. Analysis of the focus group interviews yielded three themes that describe the context in which GPs work with young people, how GPs see young people and their work with them, and GPs' expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Barriers to engaging AYAs with chronic conditions may exacerbater discontinuous primary care, but are not uncommon to this age group in primary care. (19,55,(59)(60)(61)(62) Primary care providers often report a lack of adolescent training, which may interfere with their ability to engage individuals in this age group. (61-63) Some work suggests AYAs with chronic conditions prefer to access their specialists for certain aspects of their healthcare (e.g., sexual health, mental health) and perceive family physicians as not equipped to manage these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to engaging AYAs with chronic conditions may exacerbater discontinuous primary care, but are not uncommon to this age group in primary care. (19,55,(59)(60)(61)(62) Primary care providers often report a lack of adolescent training, which may interfere with their ability to engage individuals in this age group. (61-63) Some work suggests AYAs with chronic conditions prefer to access their specialists for certain aspects of their healthcare (e.g., sexual health, mental health) and perceive family physicians as not equipped to manage these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Those at the meso level include unstable accommodation; involvement in the juvenile justice system; disability; identification as gay, lesbian, bisexual, transsexual and/or intersex; identification as part of a cultural minority group; and limited transportation (Cummings & Kang, 2012). Those at the micro level, some of which might be readily addressed, include the perceived ambiguity of, and inconsistent approaches to, managing medicolegal issues among primary care clinicians (Bartholomew, 2009); their limited knowledge and skills in youth health care (Kang et al, 2003); their sense of diffidence when working with young people (Jarrett, Dadich, Robards, & Bennett, 2011); and their limited flexibility and responsiveness (Wright & Martin, 1998). Barriers at the micro level may be exacerbated by perceptions of morality (Baruch, 1981;Stephens & Breheny, 2007)-these include a strong clinician belief in the personal responsibility of patients and/or their caregivers, and the desire of young people to present as personally and/or socially responsible individuals.…”
Section: Youth Access To Primary Carementioning
confidence: 98%
“…Tailored to the needs of GPs (Jarrett et al, 2011), the first addresses youth development; youth-friendly consultation skills, including the importance and management of patient confidentiality; and psychosocial assessment. The second module focuses on medico-legal issues, including the capacity of adolescents to consent to medical treatment, Downloaded by [Eindhoven Technical University] at 23:39 17 November 2014 parental authority for treatment, child protection and mandatory reporting, privacy and medical reports, intervention strategies, collaborative care, and youth-friendly practices.…”
Section: Youth Health Learning Modulementioning
confidence: 99%
“…[8][9][10][11][12] Youth healthcare can be a challenging area to work, partly because of limited support. [13][14][15][16] A systematic review suggested youth access to sexual and reproductive health services is hindered by service accessibility; privacy and confidentiality; and staff characteristics and competencies. 17 Another concluded that youth engagement with health systems is influenced by "the ability to recognize and understand health issues; service knowledge and attitudes toward help-seeking; structural barriers; professionals' knowledge, skills, attitudes; service environments and structures; ability to navigate the health system; youth participation; and technology opportunities".…”
Section: Youth Healthmentioning
confidence: 99%
“…Youth healthcare can be a challenging area to work, partly because of limited support . A systematic review suggested youth access to sexual and reproductive health services is hindered by service accessibility; privacy and confidentiality; and staff characteristics and competencies .…”
Section: Introductionmentioning
confidence: 99%